The role of short-chain fatty acids produced by gut microbiota in the regulation of pre-eclampsia onset - Cui, Jinghan; Wang, Jun; Wang, Ying (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Preeclampsia (PE) is a common pregnancy-related disorder characterized by disrupted maternal-fetal immune tolerance, involving diffuse inflammatory responses and vascular endothelial damage. Alterations in the gut microbiota (GM) during pregnancy can affect intestinal barrier function and immune balance. Aims and Purpose: This comprehensive review aims to investigate the potential role of short-chain fatty acids (SCFAs), essential metabolites produced by the GM, in the development of PE. The purpose is to examine their impact on colonic peripheral regulatory T (Treg) cells, the pathogenic potential of antigen-specific helper T (Th) cells, and the inflammatory pathways associated with immune homeostasis. Key Insights: An increasing body of evidence suggests that dysbiosis in the GM can lead to alterations in SCFA levels, which may significantly contribute to the development of PE. SCFAs enhance the number and function of colonic Treg cells, mitigate the pathogenic potential of GM-specific Th cells, and inhibit inflammatory progression, thereby maintaining immune homeostasis. These insights highlight the potential significance of GM dysregulation and SCFAs produced by GM in the pathogenesis of PE. While the exact causes of PE remain elusive, and definitive clinical treatments are lacking, the GM and SCFAs present promising avenues for future clinical applications related to PE, offering a novel approach for prophylaxis and therapy.